THE USE OF ICT IN IMPROVING JAPANESE LEARNERS' WORKING MEMORY CAPACITY IN DOKKAI SKILLS - Hakim, Ruri Fadhillah; Noverisa, Eva Jeniar (EDU-KATA, 2024)
In learning to read, a condition is often encountered where a person has succeeded in reaching the last line of a reading, but he does not remember what he has read. Therefore, in learning dokkai besides requiring knowledge of kanji, vocabulary, grammar and understanding, it also requires working memory or momentary memory for each sentence that is read. The purpose of this research is to determine the correlation of Working Memory Capacity of Japanese learners based on the Dokkai ability test (reading span test, then to determine the increase in Working Memory capacity of Japanese learners after the use of ICT in Dokkai learning. The method used in this research is descriptive, with a descriptive-quantitative analysis which describes the correlation of working memory in Dokkai learning and the effectiveness of using ICT to improve Dokkai abilities.